2020
DOI: 10.1021/acs.jafc.0c05551
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E Chemosensitizes Colorectal Cancer Cells via Mitigating TFAP4/Wnt/β-Catenin Signaling

Abstract: Chemoresistance and toxicity are the main obstacles that limit the efficacy of 5-fluorouracil (5-FU) in colorectal cancer (CRC) therapy. Hence, it is urgent to identify new adjuvants that can sensitize CRC cells to conventional chemotherapeutic approaches. Cucurbitacin E (CE) is a natural triterpenoid, widely distributed in dietary plants, and shows antitumor effects. Here, we report that CE enhances the sensitivity of CRC cells to chemotherapy via attenuating the expression of adenosine 5′-triphosphate (ATP)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
(96 reference statements)
1
28
0
2
Order By: Relevance
“…Previous reports have also shown that CuE has remarkable potential in suppressing the growth of multiple cancer cell types [ 18 , 30 , 31 ]. CuE can inhibit cell proliferation, induce cell cycle arrest and enhance apoptotic cell death by modulating the STAT3, MAPK, PI3K/AKT, Wnt/beta-catenin and mTOR signalling pathways [ 17 , 19 , 32 34 ]. CuE can also suppress angiogenesis by inhibiting the VEGFR2-mediated JAK2 − STAT3 signalling pathway and cancer cell metastasis by inhibiting depolymerization of actin filaments [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have also shown that CuE has remarkable potential in suppressing the growth of multiple cancer cell types [ 18 , 30 , 31 ]. CuE can inhibit cell proliferation, induce cell cycle arrest and enhance apoptotic cell death by modulating the STAT3, MAPK, PI3K/AKT, Wnt/beta-catenin and mTOR signalling pathways [ 17 , 19 , 32 34 ]. CuE can also suppress angiogenesis by inhibiting the VEGFR2-mediated JAK2 − STAT3 signalling pathway and cancer cell metastasis by inhibiting depolymerization of actin filaments [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…CuE can also suppress angiogenesis by inhibiting the VEGFR2-mediated JAK2 − STAT3 signalling pathway and cancer cell metastasis by inhibiting depolymerization of actin filaments [ 35 , 36 ]. In addition, CuE can enhance the sensitivity of tumours such as gastric cancer and colorectal cancer to conventional chemotherapeutic drugs [ 17 , 18 ]. Fortunately, our data demonstrated that CuE could inhibit HSDL2 expression and melanoma cell proliferation and induce cell apoptosis, a significant target for slowing tumour development, by suppressing the ERK and AKT pathways and reducing xenograft melanoma growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…治疗的增敏剂 [21] 。肠道微生物可通过改变药物代谢能力和宿主代谢稳态影响化 疗药的抗肿瘤疗效。有研究发现,灵芝孢子中提取的多糖通过重塑肠道菌群抑制 肿瘤细胞代谢,增强乳腺癌对紫杉醇的敏感性,并可恢复紫杉醇引发的肠道菌群 失调 [22] 。 在我国, 临床医生根据辨证施治原则常采用不同的中药方剂与化疗药相结合, 以达到肿瘤治疗减毒增效的目的。 一项对参芪扶正注射液治疗晚期胃癌的系统荟 萃分析发现,与单独采用化疗方法相比,化疗联合参芪扶正注射液可提高患者的 完全缓解(优势比 OR=1.68)和部分缓解有效率(OR=1.32),并显著改善患者 生活质量, 减少恶心、 呕吐、 口腔粘膜炎、 白细胞减少等不良反应的发生 (OR=3.05) [23] 。此外,与单独使用铂类化疗药相比,参芪扶正注射液与铂类化疗药联合治 疗晚期非小细胞肺癌(NSCLC)和结直肠癌使肿瘤治疗响应率提高 19%,并能 显著降低多种不良反应发生率 [24,25] 。 从中药薏苡仁中提取的有效成分康莱特注射 液联合化疗药治疗晚期 NSCLC 的临床试验表明,与单独使用化疗药相比,联合 用药可显著提高患者的客观响应率 (RR=1.35) , 提高患者生存质量 (RR=2.04), 并降低胃肠道副反应风险(RR=0.53) [26][27][28]…”
Section: 癌症作为全球第二大死亡因素,死亡例数和发病例数逐年上升。世界卫生组 织国际癌症研究机构(Iarc)发布的数据显示,202...unclassified
“…In addition to the aforementioned natural compounds, certain other extractions from natural products also inhibit CRC growth and induce CRC cell apoptosis via inactivation of the Wnt/β-catenin signaling pathway. Their inhibitory mechanisms in this pathway mainly include: i) Downregulating the levels of β-catenin or inhibiting nuclear translocation of β-catenin, such as TKP extracted from a medicinal plant Trichosanthes kirilowii ( 2 ), magnolol derived from Magnolia obovata ( 135 ), ethanol extract of Scutellaria barbata D. Don (EESB) ( 136 ), jatrorrhizine (a main component of Rhizoma coptidis ) ( 46 ) and pristimerin (a natural triterpenoid) ( 137 ); ii) downregulating phosphosylated-GSK-3β or upregulating GSK-3β, for example TKP ( 138 ); iii) inhibiting the expression of Wnt downstream target genes, including magnolol ( 135 ), EESB ( 136 ), sulforaphane extracted from cruciferous vegetables ( 18 ) and pristimerin ( 137 ); iv) blocking the interaction between β-catenin and TCF4 complexes, such as magnolol ( 135 ) and 11α, 12α-epoxyleukamenin E isolated from Salvia cavaleriei ( 37 ); v) downregulating invasion-associated proteins MMP-2 and MMP-9, such as TKP ( 138 ); vi) inhibiting EMT via increasing E-cadherin and decreasing N-cadherin, such as jatrorrhizine ( 46 ); and vii) exerting a synergistic effect on the inhibition of CRC, for example, the combination of cucurbitacin E and 5-FU inhibits the expression of β-catenin and chemosensitizes CRC cells via negatively regulating the transcription factor AP4/Wnt/β-catenin axis ( 139 ).…”
Section: Therapeutic Strategies Targeting Wnt/β-catenin Signaling For Crcmentioning
confidence: 99%